PENINGKATAN PEMAHAMAN DAN PENGIMPLEMENTASIAN WISATA ISLAMI BAGI PELAKU WISATA DI KOTA PADANG - Wardi, Yunia; Abror, Abror; Trinanda, Okki Tri (Universitas Pendidikan Ganesha, 2017)
Islamic tourism is considered to have a very good prospect in the development of tourism in Indonesia, especially in the city of Padang. This assessment came about because of the culture of the people in the Islamic city of Padang. But despite the huge potential, there are still some problems related to the service. Whereas the implementation of good Islamic tourism is with the integration of various aspects of tourism services that exist. That is starting from the promotion of tourism, tourism service itself until the tourists are back again to their respective regions. Based on the background of the importance of Islamic tourism services in the tourist areas above, the activities of community service in the form of Islamic tourism service training is implemented, to provide insight into aspects of excellent service to tourists who make the tourist area more attractive and satisfying . As for the object of community service activities is the actors of tourism that deal directly with the tourists who come to the city of Padang. Namely the managers of travel bureaus, hotels, guides, guides, taxi drivers, and other parties. With the implementation of this activity, tourism actors have a good understanding of the concept and importance of Islamic Tourism, so they can integrate various tourist services to create a good Islamic tourism experience for tourists.